2013
DOI: 10.3109/02713683.2013.774422
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography for Measuring the Tear Film Meniscus: Correlation with Schirmer Test and Tear-Film Breakup Time

Abstract: OCT values were significantly lower in patients with Schirmer values of <5 mm. Tear meniscus measurements obtained by OCT are reliable for establishing a diagnosis of dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 35 publications
0
29
0
6
Order By: Relevance
“…[215] Furthermore, they proceeded to test the role of OCT-derived TMH measurements in assessing response to punctal plug therapy for dry eye, which confirmed TMH as a quick and sensitive parameter in the diagnosis and therapeutic assessment of dry eye. [227] Other groups have confirmed the correlation of AS-OCT tear film biometry with Schirmer's test,[228] while retaining high reliability of central tear film measurements (intraclass correlation coefficient = 0.97), making AS-OCT a reliable, precise and accurate tool in tear film biometry. [229] However, it is worthwhile to note that tear film biometry may not be useful in the assessment of MGD-dependent EDE.…”
Section: Diagnostic Imaging In Dry Eye Diseasementioning
confidence: 98%
“…[215] Furthermore, they proceeded to test the role of OCT-derived TMH measurements in assessing response to punctal plug therapy for dry eye, which confirmed TMH as a quick and sensitive parameter in the diagnosis and therapeutic assessment of dry eye. [227] Other groups have confirmed the correlation of AS-OCT tear film biometry with Schirmer's test,[228] while retaining high reliability of central tear film measurements (intraclass correlation coefficient = 0.97), making AS-OCT a reliable, precise and accurate tool in tear film biometry. [229] However, it is worthwhile to note that tear film biometry may not be useful in the assessment of MGD-dependent EDE.…”
Section: Diagnostic Imaging In Dry Eye Diseasementioning
confidence: 98%
“…110 TMH has been shown to correlate with DED and the traditional measurements for DED. 97,110120 Some studies suggest there is good repeatability and reproducibility of TMH measurements in DED and normals. 101,114,115,118,120122 However, TMH taken with different machines may not be comparable.…”
Section: Point Of Care Biomarkersmentioning
confidence: 99%
“…120,122 They also have been shown to correlate with DED and traditional measurements for DED. 116,119,120 However, TMA and TMD measurements using OCT have not yet been incorporated in any multicenter clinical trial.…”
Section: Point Of Care Biomarkersmentioning
confidence: 99%
“…The results showed that dry eye patients with punctal plugs have higher tear meniscus heights. Studies have shown that OCT is a reproducible, objective, and noninvasive instrument for measuring the tear lake 61,62. Of interesting potential value is the ability to measure tear film thickness using OCT. One study found highly reproducible measurements using ultrahigh resolution OCT.…”
Section: Emerging Technologies For Diagnosismentioning
confidence: 99%